2007
DOI: 10.1088/0953-4075/40/17/004
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution study of resonant Auger decay processes in N2O after core electron excitation from terminal nitrogen, central nitrogen and oxygen atoms to the 3π LUMO

Abstract: Decay spectra of N 2 O following excitation to the N terminal (N t ) → π * , N central (N c ) → π * and O 1s → π * intermediate states are reported. The final states reached after participator decay show resonant enhancement consistent with a local-density-of-states analysis based on the Mulliken population of the valence molecular orbitals. In particular, the X-state is resonantly enhanced mostly after excitation from the N t 1s and the O 1s core levels to the π * , while the B-state is mostly enhanced follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Spectator lines with constant kinetic energy may come from states where the potential energy surfaces of the intermediate and the final states are parallel. 59 At the B2 position, no new peaks enter the spectrum. At the T2 position, a new peak at 2115.4 eV appears.…”
Section: ■ Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Spectator lines with constant kinetic energy may come from states where the potential energy surfaces of the intermediate and the final states are parallel. 59 At the B2 position, no new peaks enter the spectrum. At the T2 position, a new peak at 2115.4 eV appears.…”
Section: ■ Resultsmentioning
confidence: 97%
“…At the T1 position, new dispersing lines can be observed at 2115 and 2118.3 eV, overlapping with the constant kinetic energy lines present at those positions. Spectator lines with constant kinetic energy may come from states where the potential energy surfaces of the intermediate and the final states are parallel . At the B2 position, no new peaks enter the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The bars correspond to the main dication states reported in Table I has been proposed and applied successfully for several polyatomic molecules. 5,7,9 In the present case, the comparison has been guided by recent combined experimental and theoretical studies of the valence shell electronic structure by photoabsorption spectroscopy 30 and of the Auger spectrum of pyrimidine and halopyrimidines by electron impact. 19 The comparison between the N/C (1s) → π * RAE spectra and the corresponding N/C (1s) Auger electron spectra is reported in Figures 6(a) and 6(b), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As it will be shown in this work, RAE spectroscopy also provides a feedback for these complementary studies, which will benefit from the new information provided to sort out ambiguous assignments. RAE measurements with site-selectivity were performed in a series of condensed phase azabenzenes 4 and gas phase butadiene, 5 furan, 6 formic acid, acetaldehyde, acetic acid, methyl formate, 7 methyl oxirane, 8 and nitrous oxide, 9 at the C, N, and O K-edges depending on the molecule. All of these studies have shown the importance of the localization of the core excitation in the evolution of the system.…”
Section: Introductionmentioning
confidence: 99%
“…而半 个多世纪以来, 同步辐射光 [2] 、激光 [3,4] 、自由电子激 光 [5][6][7] 等先进光源技术的发展, 为原子分子物理研究 提供了更强有力的激发源. 实验探测手段包括光吸收 谱 [8] 、电子能谱 [9] 、离子质谱 [10] 、电子/离子成像 [11] 、 以及多粒子符合测量 [12][13][14][15] . 另外电子碰撞方法是光吸 收方法有益的补充 [1] .…”
Section: 引言unclassified